INDUSTRIAL IOT FOR ARCHITECTS AND ENGINEERS : architecting secure, robust, and scalable ... industrial iot solutions with aws - Bernal, Joey (PACKT Publishing Limited, 2023)
Go beyond connecting services to understand the unique challenges encountered in industrial environments by building Industrial IoT architectures using AWS Purchase of the print or kindle book includes a free eBook in the PDF format Key Features Understand the key components of IoT Architecture and how it applies to Industry 4.0 Walk through extensive examples and solutions across multiple Industries Learn how to collect, process, store, and analyse Industrial IoT data Book Description When it comes to using the core and managed services available on AWS for making decisions about architectural environments for an enterprise, there are as many challenges as there are advantages. This Industrial IoT book follows the journey of data from the shop floor to the boardroom, identifying goals and aiding in strong architectural decision-making. You'll begin from the ground up, analyzing environment needs and understanding what is required from the captured data, applying industry standards and conventions throughout the process. This will help you realize why digital integration is crucial and how to approach an Industrial IoT project from a holistic perspective. As you advance, you'll delve into the operational technology realm and consider integration patterns with common industrial protocols for data gathering and analysis with direct connectivity to data through sensors or systems. The book will equip you with the essentials for designing industrial IoT architectures while also covering intelligence at the edge and creating a greater awareness of the role of machine learning and artificial intelligence in overcoming architectural challenges. By the end of this book, you'll be ready to apply IoT directly to the industry while adapting the concepts covered to implement AWS IoT technologies. What you will learn Discover Industrial IoT best practices and conventions Understand how to get started with edge computing Define and build IoT solution architectures from scratch Use AWS as the core of your solution platform Apply advanced analytics and machine learning to your data Deploy edge processing to react in near real time to events within your environment Who this book is for This book is for architects, engineers, developers, and technical professionals interested in building an edge and cloud-based Internet of Things ecosystem with a focus on industry solutions. Since the focus of this book is specifically on IoT, a solid understanding of core IoT technologies and how they work is necessary to get started. If you are someone with no hands-on experience, but are familiar with the subject, you'll find the use cases useful to learn how architectural decisions are made.